Biomechanical analysis of all-polyethylene total knee arthroplasty on periprosthetic tibia using the finite element method. (June 2022) - Apostolopoulos, Vasileios; Tomáš, Tomáš; Boháč, Petr; Marcián, Petr; Mahdal, Michal; Valoušek, Tomáš; Janíček, Pavel; Nachtnebl, Luboš
Highlights: Computational modeling demonstrates the mechanical performance of periprosthetic tibia with all-polyethylene TKA. Geometry, material, and load representation of the bone tissues based on CT data and clinical observation. The cancellous bone tissue has a heterogeneous distribution of elastic constants obtained from the CT datasets. Age does not significantly affect the biomechanical response. Based on the results, the all-polyethylene TKA will stimulate the bone formation of the periprosthetic tibia. Abstract: Background and objective: Total knee arthroplasty (TKA) with modern all-polyethylene tibial (APT) components has shown high long-term survival rates and comparable results to those with metal-backed tibial components. Nevertheless, APT components are primarily recommended for older and low-demand patients. There are no evidence-based biomechanical guidelines for orthopaedic surgeons to determine the appropriate lower age limit for implantation of APT components. A biomechanical analysis was assumed to be suitable to evaluate the clinical results in patients under 70 years. The scope of this study was to determine biomechanically the appropriate lower age limit for implantation of APT components. Methods: To generate data of the highest possible quality, the geometry of the computational models was created based on computed tomography (CT) images of a representative patient. The cortical bone tissue model distinguishes the change in mechanical properties described in three parts from the tibial cut. The cancellous bone material model has a heterogeneous distribution of mechanical properties. The values used to determine the material properties of the tissues were obtained from measurements of a CT dataset comprising 45 patients. Results: Computational modeling showed that in the majority of the periprosthetic volume, the von Mises strain equivalent ranges from 200 to 2700 με; these strain values induce bone modeling and remodeling. The highest measured deformation value was 2910 με. There was no significant difference in the induced mechanical response between bone models of the 60-year and 70-year age groups, and there was <3% difference from the 65-year age group. Conclusions: Considering in silico limitations, we suggest that APT components could be conveniently used on a bone with mechanical properties of the examined age categories. Under defined loading conditions, implantation of TKA with APT components is expected to induce modeling and remodeling of the periprosthetic tibia. Following clinical validation, the results of our study could modify the indication criteria of the procedure, and lead to more frequent implantation of all-polyethylene TKA in younger patients.